A Novel Predictive Model for Idiopathic Multicentric Castleman Disease: The International Castleman Disease Consortium Study. (18th September 2020) - Yu, Li; Shi, Menghan; Cai, Qingqing; Strati, Paolo; Hagemeister, Fredrick; Zhai, Qiongli; Li, Ling; Fang, Xiaosheng; Li, Jianyong; Sun, Ruifang; Zhang, Shanxiang; Yang, Hanjin; et al.
Abstract: Background: Patients with multicentric Castleman disease (MCD) who are negative for human immunodeficiency virus and human herpesvirus 8 are considered to have idiopathic MCD (iMCD). The clinical presentation of iMCD varies from mild constitutional symptoms to life‐threatening symptoms or death. The treatment strategy varies from "watchful waiting" to high‐dose chemotherapy. This diverse clinical presentation calls for a classification stratification system that takes into account the severity of the disease. Subjects, Materials, and Methods: We analyzed the clinical, laboratory, and pathologic abnormalities and treatment outcomes of 176 patients with iMCD (median follow‐up duration 12 years) from the U.S. and China to better understand the characteristics and prognostic factors of this disease. This discovery set of iMCD results was confirmed from the validation set composed of additional 197 patients with iMCD organized from The International Castleman Disease Consortium. Results: Using these data, we proposed and validated the iMCD international prognostic index (iMCD‐IPI), which includes parameters related to patient characteristics (age > 40 years), histopathologic features (plasma cell variant), and inflammatory consequences of iMCD (hepatomegaly and/or splenomegaly, hemoglobin <80 g/L, and pleural effusion). These five factors stratified patients according to their performance status and extent of organ dysfunction into three broad categories: low risk, intermediate risk, and high risk. The iMCD‐IPI score accurately predicted outcomes in the discovery study cohort, and the results were confirmed on the validation study cohort. Conclusion: This study represents the largest series of studies on patients with iMCD in the field and proposed a novel risk‐stratification model for iMCD‐IPI that could be used to guide risk‐stratified treatment strategies in patients with iMCD. Implications for Practice: Patients with idiopathic multicentric Castleman disease (iMCD) can benefit from care based on clinical symptoms and disease severity. This study in 176 patients with iMCD constructed an iMCD‐IPI score based on five clinical factors, including age >40 years, plasmacytic variant subtype, hepatomegaly and/or splenomegaly, hemoglobin <80 g/L, and pleural effusion, and stratified patients into three risk categories: low risk, intermediate risk, and high risk. The predictive value was validated in an independent set of 197 patients with iMCD from The International Castleman Disease Consortium. The proposed novel model is valuable for predicting clinical outcome and selecting optimal therapies using clinical parameters. Abstract : This cooperative study analyzed the clinical, laboratory, and pathologic variables of patients with idiopathic multicentric Castleman disease (iMCD), resulting in a proposal for an iMCD international prognostic index that can help physicians agree on a treatment algorithm for iMCD.